2012
DOI: 10.1177/1079063212438922
|View full text |Cite
|
Sign up to set email alerts
|

Comparing a Pictorial Stroop Task to Viewing Time Measures of Sexual Interest

Abstract: This study investigated the ability of two viewing time (VT) methodologies and a pictorial Stroop task to differentiate sexual interest in a group of nonoffending heterosexual and homosexual men. The two VT methodologies were investigated given the lack of consistency among published studies supporting this method. The results indicated that the VT methodology in which participants are asked to browse through some images is slightly superior to the method in which participants are asked to rate their attractiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Results in a separate study of 35 men, 11 of who were homosexual and 24 were heterosexual, reporting no history of child sexual offenses indicated a discriminatory ability between heterosexual men and homosexual men using female stimuli, but could not discriminate among preferred ages. The authors suggested that other mechanisms are responsible for rating child stimuli, thus decreasing the validity for this test among pedophilic participants (Bourke and Gormley, 2012 ).…”
Section: Pedophilia and Pedophilic Disorder: A Psychological Perspectmentioning
confidence: 99%
“…Results in a separate study of 35 men, 11 of who were homosexual and 24 were heterosexual, reporting no history of child sexual offenses indicated a discriminatory ability between heterosexual men and homosexual men using female stimuli, but could not discriminate among preferred ages. The authors suggested that other mechanisms are responsible for rating child stimuli, thus decreasing the validity for this test among pedophilic participants (Bourke and Gormley, 2012 ).…”
Section: Pedophilia and Pedophilic Disorder: A Psychological Perspectmentioning
confidence: 99%
“…One possible explanation for this pattern of results is that the sexual stimuli produce a grabbing of attention that also ties up processing for some time, hence, there are not enough resources to process the dot stimuli or for decision making (Geer & Bellard, 1996 ; Wright & Adams, 1994 ). The situation may be analogous to an “emotional Stroop” effect whereby the emotional content of the stimulus is processed with greater priority than other aspects of the image (Bourke & Gormley, 2012 ; Ciardha & Gormley, 2012 ; Gress, Anderson, & Laws, 2013 ). It is notable that Wright and Adams ( 1994 ) also found that the detection of a dot within a sexual picture (rather than after a sexual picture) was found to be slower for images containing their preferred sex, and this was found for both men and women that were either heterosexual or homosexual.…”
Section: Introductionmentioning
confidence: 99%
“…Higher mean response latencies in trials with targets of specific sex or sexual maturity are then interpreted as indicating the sexual interests of the individual. In spite of profound support for the validity of VT tasks in assessing sexual orientation (e.g., Bourke & Gormley, 2012;Ebsworth & Lalumière, 2012;Imhoff et al, 2010;Imhoff et al, 2011, Study 1;Israel & Strassberg, 2009;Lippa, 2012;Quinsey, Ketsetzis, Earls, & Karamanoukian;Zamansky, 1956), the underlying mechanisms have not been finally clarified. However, Imhoff et al (2010) experimentally ruled out deliberate delay of response latencies and interfering attentional adhesion effects due to the sexually attractive nature of relevant target stimuli.…”
Section: Task-relevant Measuresmentioning
confidence: 99%